Utilization of Information Technology at the Mangarabombang District Office - Muh. Nasrullah; Andi Agustang; Andi Muhammad Idhan; Nur Azizah B (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Information technology brings together high-speed computing and communications for data, voice, and video. This study aims to determine the use of information technology at the Mangarabombang District Office, Takalar Regency, which focuses on managing Family Cards. To find out these objectives, the researchers used a qualitative descriptive type of research. There were 9 informants in this study and used data collection techniques that were carried out through observation, interviews, and documentation. The data obtained from the research results are processed using data analysis techniques, namely data collection, data reduction, data presentation, conclusion/verification. The results showed that the utilization of information technology at the Mangarabombang District Office, Takalar Regency was optimal. Viewed from the aspect of facilitating communication and obtaining information, developing skills and awareness, increasing the quality and quantity of services, encouraging the growth of democracy. This research can be used as a reference in the realm of using information technology at the sub-district level, because previous research has focused on the district or city level.